1983
DOI: 10.1088/0034-4885/46/11/001
|View full text |Cite
|
Sign up to set email alerts
|

Parton models of low momentum transfer processes

Abstract: In the last five years ample evidence has been found supporting the idea that the quark-parton structure of hadrons is relevant for multiple production in soft hadronic collisions. Starting from the experimental foundations, we compare the most successful models applying this idea. Implications are discussed on special type reactions like diffraction dissociation and collisions on nuclei, and the models are confronted with recent data leading to new insight and modifications. Relative yields of particles in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

1985
1985
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 338 publications
0
21
1
1
Order By: Relevance
“…In order to apply such a hadronization scheme also to soft hadron-hadron interactions, we have to make the basic assumption that quark and antiquark jets from e+e-annihilation or diquark jets from lepton-hadron scattering processes do not differ strongly from the ones produced in hadron-hadron collisions. This jet universality is not derived theoretically, but experimental data strongly suggest such an assumption, see [9] for a review.(iii) For chains of very low invariant mass we slightly modify the kinematics and create directly stable hadrons or hadron resonances.-2 -(iv) Transforming all created hadrons and hadron resonances back into the laboratory system, we obtain a complete final hadronic state.Since we use a Monte-Carlo method we are able to generate exclusive events conserving exactly energy momentum and all additive quantum numbers.(v) The subsequent decay of hadron resonances into stable final hadrons is realized using the Monte-Carlo code DECAY [10].Since we are only interested in multiparticle production in the energy range from 5 or 10 GeV up to 1 TeV, it is sufficient to consider two chains containing only the valence quarks in hadron-hadron collisions. This is not correct for larger energies, i.e.…”
mentioning
confidence: 99%
“…In order to apply such a hadronization scheme also to soft hadron-hadron interactions, we have to make the basic assumption that quark and antiquark jets from e+e-annihilation or diquark jets from lepton-hadron scattering processes do not differ strongly from the ones produced in hadron-hadron collisions. This jet universality is not derived theoretically, but experimental data strongly suggest such an assumption, see [9] for a review.(iii) For chains of very low invariant mass we slightly modify the kinematics and create directly stable hadrons or hadron resonances.-2 -(iv) Transforming all created hadrons and hadron resonances back into the laboratory system, we obtain a complete final hadronic state.Since we use a Monte-Carlo method we are able to generate exclusive events conserving exactly energy momentum and all additive quantum numbers.(v) The subsequent decay of hadron resonances into stable final hadrons is realized using the Monte-Carlo code DECAY [10].Since we are only interested in multiparticle production in the energy range from 5 or 10 GeV up to 1 TeV, it is sufficient to consider two chains containing only the valence quarks in hadron-hadron collisions. This is not correct for larger energies, i.e.…”
mentioning
confidence: 99%
“…As is shown in Fig. 10, the average shape of the hadronic system is the same in all three types of collision at given hadronic energy [13], as is its quite dramatic change with energy. Of course, a higher energy hadronic point would be needed to see where flattening-off takes place, there.…”
Section: Je T Universalitymentioning
confidence: 53%
“…The power ra of the (1 -ja:|)n parametrization of the invariant single-particle inclusive cross section, compared to the dimensional counting rules (lines). The broken lines are corrected for the sup pression of d-quarks in the proton structure function [13].…”
Section: 3 Dimensional Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a ratio for charged pions has often been fit to the form R = 1 +/3( vp -1 1. In the absence of rescattering, it is expected [20] that /3 should equal 0.5, and if rescattering does contribute significantly, than /3 should be greater. In our own previous work [ l l ] , we found that for charged pions, / 3 was consistent with 0.5 for each of our three beams.…”
Section: 7k04mentioning
confidence: 99%